Assessing student’s industrial attachment through online portfolio / Fariz Aswan Ahmad Zakwan … [et al.] - Ahmad Zakwan, Fariz Aswan; Abdul Karim, Nurulzatushima; Sadikon, Siti Fatimah; Tukiar, Mohd. Azuan; Hasan, Daliah; Musir, Adhilla Ainun; Ahmad, Hazrina; Ismail, Ruqayyah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Faculty of Civil Engineering (FCE), Universiti Teknologi MARA (Pulau Pinang) has been implementing the Outcome Based Learning (OBE) in teaching and learning since year 2007. Since FCE is offering a degree programme, therefore it has to be accredited by the Engineering Accreditation Council (EAC). OBE focuses on the development of the student’s soft skills with the intention of preparing them to face the real working environment. This paperless student portfolio is one of the faculty's initiatives in ensuring the student learning reflection and soft skills been captured and documented well for continuous quality improvement of the program. This portfolio has undergone few phases of improvement where FCE keeps improving the content and structure to meet the needs of accreditation and will further benefit the students especially in increasing their employability. The latest improvement is that this portfolio now also functions as the students Industrial Training Log Book, whereas all the knowledge, pictures and data from their industrial training will be captured and documented in a proper manner. With well documented portfolio which can be assessed anywhere, it will be a strong compilation of students archive that can be their supported document when applying for a job after they have graduated.